Pengembangan Instrument Self-Regulated Learning Pada Pembelajaran Ilmu Pengetahuan Sosial Siswa Sekolah Dasar - Sa'idah, Niswatus; Mhmd Habibi (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This research aims to develop a self-regulated learning instrument for social studies learning for grade 3 elementary school students. The urgency of self-regulated learning instruments is to help improve learning outcomes by setting learning goals and monitoring effectiveness by growing self-confidence in students. This research aims to measure the level of validity and reliability of self-regulated learning instruments. The indicators for self-regulated learning are learning planning, learning motivation, metacognition, learning behaviour and learning evaluation. This research uses the Research and Development (R & D) research method with a 4D development model which is simplified to 3D. This research involved 17 respondents, namely 3rd grade students at SD BPMAA Pekanbaru. The form of the instrument developed is in the form of a statement totalling 31 statements. Analysis of the validity and reliability of this instrument uses SPSS version 25.00 for Windows. As for the results of the validity of the instrument with the r table value with a total of 17 students as respondents, for df (N-2) at the 0.05 significance level it is 0.4821, so of the 31 statement items 26 items are valid and 5 items are invalid. For instrument reliability results, namely if sig. more than 0.60 then it is declared reliable and can be used. So according to the results of the reliability analysis with Cronbach's alpha 0.923, this self-regulated learning instrument is declared reliable and can be used. So, it can be concluded that the instrument developed can be used to measure self-regulated learning in grade 3 elementary school students.